METHOD FOR REMOVING DEPOSIT IN HIGH-TEMPERATURE OVEN - FUSESHIRO SHIYUUJI; KOBAYASHI YOSHIJI; MIYATA KATSUAKI (1992)
PURPOSE:To enable the removal of the subject deposit without stopping the operation of a furnace by parallelly arranging plural dragging ropes in a state separated from each other, passing the ropes through a furnace in a movable manner, attaching a cleaning member to the ropes and pulling the cleaning member into the furnace to clean the inlet and outlet parts of the furnace. CONSTITUTION:In the case of threading carbon fibers F, etc., through a high- temperature furnace such as graphitization furnace 8 before baking treatment, two or more dragging ropes 2A, 2B arranged in parallel in mutually separated state are movably passed through the graphitization furnace 8 in stretched state. A cleaning member 100 is attached to the dragging ropes and pulled into the furnace 8 from the inlet port 8a by moving the dragging ropes 2A, 2B from the inlet port 8a toward the outlet port 8b. After passing through the furnace 8, the cleaning member 100 is taken out through the outlet port 8b to complete the removal of the deposit D deposited in the inlet and outlet regions 8a, 8b of the furnace 8.